Growth of knowledge on the reptiles of India, with an introduction to systematics, taxonomy and nomenclature - Das, I. (Bombay :The Society, 2003)
The progress in our understanding of the contents of the reptile fauna of India is reviewed. The early classification of the fauna was undertaken during Vedic times, and included groupings based on form, medium occupied, sensory powers and whether wild or domesticated. The Linnean system of binomial nomenclature, adopted since 1758, is the most widely used scheme of classification, but has its limitations, chiefly in being incompatible with the principle of common descent. Phylogenetic and other classifications, based on natural groups, have lead to a proliferation of studies on systematics, from the traditional studies of morphology and anatomy, to the use of more modem molecular techniques. Aspects of systematics, taxonomy and nomenclature are discussed for non-systematists. The last stocktaking of the reptile fauna of India, in the three volume Fauna of British India series by Malcolm Smith is compared with the fauna now known from the country. A general conclusion reached is that there is much to be learnt of the country’s highly diverse and endemic reptile fauna, but efforts need to be accelerated in the face of loss of habitats as a result of deforestation and of systematic expertise itself, with cuts in research funding and realignment of policies on basic research.